Body fatness in sedentary and active students with different body mass index - Malara Marzena; Lutosławska Grażyna; Mazurek Krzysztof; Kęska Anna; Tkaczyk Joanna (Sciendo, 2021)
Study aim: Numerous data have indicated that body fat stores undergo complicated regulation by genetic and environmental factors, including physical activity. However, the majority of studies did not take into account this aspect of lifestyle in proposed body fat limits. In this context it seems that a more precise and reliable classification of body fat is provided by the American Council on Exercise (ACE), which distinguishes individuals not only with respect to sex but also activity level.